The impact of primary ciliary dyskinesia on female and male fertility: a narrative review. (31st January 2023) - Newman, Lydia; Chopra, Jagrati; Dossett, Claire; Shepherd, Elizabeth; Bercusson, Amelia; Carroll, Mary; Walker, Woolf; Lucas, Jane S; Cheong, Ying
Abstract: BACKGROUND: Primary ciliary dyskinesia (PCD) is a genetic condition affecting the structure and function of sperm flagellum and motile cilia including those in the male and female reproductive tracts. Infertility is a commonly reported feature of PCD, but there is uncertainty as to how best to counsel patients on their fertility prognosis. OBJECTIVE AND RATIONALE: This review aimed to summarize the prevalence of subfertility, possible underlying mechanisms, and the success of ART in men and women with PCD. The efficacy of ART in this patient group is relatively unknown and, hence, the management of infertility in PCD patients remains a challenge. There are no previous published or registered systematic reviews of fertility outcomes in PCD. SEARCH METHODS: Systematic literature searches were performed in Medline, Embase, Cochrane Library, and PubMed electronic databases to identify publications between 1964 and 2022 reporting fertility outcomes in men and women with PCD. Publications were excluded if they reported only animal studies, where gender was not specified or where subjects had a medical co-morbidity also known to impact fertility. Quality of evidence was assessed by critical appraisal and application of an appraisal tool for cross-sectional studies. The primary outcomes were natural conception in men and women with PCD, and conception following ART in men and women with PCD. OUTCOMES: A total of 1565 publications were identified, and 108 publications were included after screening by two independent researchers. The quality of available evidence was low. The exact prevalence of subfertility in PCD is unclear but appears to be higher in men (up to 83% affected) compared to women (up to 61% affected). Variation in the prevalence of subfertility was observed between geographic populations which may be explained by differences in underlying genotype and cilia function. Limited evidence suggests subfertility in affected individuals is likely caused by abnormal cilia motion in the fallopian tubes, endometrium and efferent ductules, and dysmotile sperm. Some men and women with PCD benefited from ART, which suggests its use should be considered in the management of subfertility in this patient group. Further epidemiological and controlled studies are needed to determine the predictors of fertility and optimal management in this patient group. WIDER IMPLICATIONS: It is important that patients with PCD receive evidence-based counselling about the potential impact of their condition on their fertility prognosis and what management options may be available to them if affected. Understanding the pathophysiology and optimal management of subfertility in PCD will increase our understanding of the role of cilia and the impact of wider secondary ciliopathies on reproduction. Graphical abstract: